Ordered mesoporous Co3O4-Al2O3 bimetal oxides for CO2 hydrogenation to synthetic natural gas: Effects of surface Al2O3 distribution. (1st July 2023) - Park, Yong Min; Kim, Byeong Gi; Gao, Xinhua; Zhang, Xingjun; Roh, Hyun-Seog; Chung, Chan-Hwa; Bae, Jong Wook
Graphical abstract: Highlights: Mesoporous Co3 O4 -Al2 O3 showed good CO2 hydrogenation activity to CH4 at ∼6 wt%Al. Adjusted surface hydrophobicity at an optimal amount of spinel CoAl2 O4 was crucial factor. Oxygen vacant sites suppress competitive adsorption of water formed by CO2 hydrogenation. Abstract: The highly ordered mesoporous structures of Co3 O4 -Al2 O3 mixed metal oxide, prepared by using a hard template of the mesoporous KIT-6, revealed a higher catalytic activity and stability for CO2 hydrogenation to synthetic methane at an optimal surface Al content with ∼6 wt% (m-CoAl(1)). The higher CO2 conversion (42.5%) and CH4 selectivity (96.7%) were attributed to the adjusted surface hydrophobicity with optimal amount of spinel CoAl2 O4 phases, where the CoAl2 O4 phases mainly acted as structural stabilizing components in the ordered mesoporous Co3 O4 -Al2 O3 matrices by suppressing the aggregations of Co3 O4 nanoparticles as well as by generating more hydrophobic surfaces. At an optimal surface Al2 O3 content (m-CoAl(1)), the stronger interactions of Co3 O4 -Al2 O3 were selectively formed with the help of an optimal amount of the spinel CoAl2 O4 phases, which further enhanced the surface hydrophobicity and oxygen vacant sites to effectively suppress competitive adsorption of water formed by CO2 hydrogenation.